2014
DOI: 10.1093/mnras/stu864
|View full text |Cite
|
Sign up to set email alerts
|

Periodic mass loss from viscous accretion flows around black holes

Abstract: We investigate the behaviour of low angular momentum viscous accretion flows around black holes using Smooth Particle Hydrodynamics (SPH) method. Earlier, it has been observed that in a significant part of the energy and angular momentum parameter space, rotating transonic accretion flow undergoes shock transition before entering in to the black hole and a part of the post-shock matter is ejected as bipolar outflows, which are supposed to be the precursor of relativistic jets. In this work, we simulate accreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 57%
“…Numerical simulations show that the post-shock disc is the jet base (Molteni et al 1996b;Das et al 2014). Numerical simulations also show that the angular momentum at the top of the PSD (the base of the jet) is about 20-30% less than from the equatorial plane, so without losing generality we consider at the base λ j = 2λ/3, and the location of the jet base x b = (r ci + r sh )/2.…”
Section: To Find Jet Critical Point and Mass Outflow Ratementioning
confidence: 99%
“…It has been shown earlier that VZS are the surfaces of constant angular momentum and also of constant entropy for fluid flow above the equatorial plane (Chakrabarti 1985). In addition, numerical simulations showed that the entire PSD generates bipolar jets (Molteni et al 1996b;Lanzafame et al 1998;Das et al 2014;Lee et al 2016). So, we choose the foot point (r b ) of the jet streamline located half way between the accretion shock and inner critical point of the disc, but on the surface of PSD.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…This assumption has been dictated by a large number of simulations, which showed SKD to have a flatter surface compared to PSD (Molteni et al 1994(Molteni et al , 1996Giri & Chakrabarti 2013;Das et. al.…”
Section: Accretion Disc and Radiative Momentsmentioning
confidence: 99%
“…Generally most of the papers which investigate the interaction of jet with disc photons do not consider the issue of the launch mechanism of jets in terms of the accretion properties. In the advective disc regime, numerical simulations first showed that the extrathermal gradient force in the PSD automatically generates bipolar outflows (Molteni et al 1994(Molteni et al , 1996Das et. al.…”
Section: Introductionmentioning
confidence: 99%